A productive role for science in assisted colonization policy. (25th July 2016) - Neff, Mark W.; Carroll, Katherine
Abstract : Assisted colonization—the intentional movement of species as a climate adaptation strategy—has emerged as a divisive controversy in the conservation biology literature. We review selected scientific literature to understand the nature of the controversy, alongside relevant scholarship on the science‐policy interface to highlight ways in which scientists and their work might most effectively and appropriately inform decisions on this management strategy. The scientific literature thus far is problematic in two ways that threaten to undermine the utility of science to actual decision‐making processes: As a collection, it contains abundant and seemingly incommensurable insights about assisted colonization. This is at least in part a product of nature, which is sufficiently diverse to provide examples and case studies that appear to justify any number of policy preferences regarding ecosystem management. This first shortcoming exacerbates the second: Scientific authors thus far have not adequately addressed the value‐based considerations implicit in their own work, nor acknowledged public's legitimate standing in these inherently value‐based decisions. In combination, these attributes of the literature ensure that additional knowledge on assisted colonization will exacerbate public controversy—rather than dispel it—when public attention increases. We propose that if scientists appropriately disentangle value considerations from technical ones, invite public debates over values, and treat proposals individually rather than debating the approach writ‐large, they stand to have the greatest influence over technical aspects of decision processes. Scientists would serve themselves well to acknowledge the limits of science and embrace public dialogue about specific management proposals. WIREs Clim Change 2016, 7:852–868. doi: 10.1002/wcc.420 This article is categorized under: Climate, Ecology, and Conservation > Extinction Risk Social Status of Climate Change Knowledge > Climate Science and Decision Making